2022
DOI: 10.3390/microorganisms10071431
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of an Easy Laboratory Method for the Concentration of Oocysts and Commercial DNA Isolation Kits for the Molecular Detection of Cyclospora cayetanensis in Silt Loam Soil Samples

Abstract: Cyclospora cayetanensis is a protozoan parasite that causes foodborne outbreaks of diarrheal illness (cyclosporiasis) worldwide. Contact with soil may be an important mode of transmission for C. cayetanensis and could play a role in the contamination of foods. However, there is a scarcity of detection methods and studies for C. cayetanensis in soil. Traditional parasitology concentration methods can be useful for the detection of C. cayetanensis, as found for other protozoa parasites of similar size. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 34 publications
(87 reference statements)
2
17
0
Order By: Relevance
“…Thus, bead-beating, emerged as the most effective method for rupturing the tough structure of the oocyst wall while also preserving genomic material by not causing excessive DNA shearing or hydrolysis. This finding aligns with other studies investigating Cryptosporidium and other parasites across various matrices ( Babaei et al, 2011; Amoah et al, 2019; Temesgen et al, 2020; Shipley et al, 2022 ). Compared to other pretreatments, bead-beating not only improved DNA extraction but also enhanced PCR sensitivity, offering a rapid, cost effective, and straightforward approach for sample preparation (Elwin et al, 2014; Lindergard et al, 2003; Scharf et al, 2020; Shipley et al, 2022).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, bead-beating, emerged as the most effective method for rupturing the tough structure of the oocyst wall while also preserving genomic material by not causing excessive DNA shearing or hydrolysis. This finding aligns with other studies investigating Cryptosporidium and other parasites across various matrices ( Babaei et al, 2011; Amoah et al, 2019; Temesgen et al, 2020; Shipley et al, 2022 ). Compared to other pretreatments, bead-beating not only improved DNA extraction but also enhanced PCR sensitivity, offering a rapid, cost effective, and straightforward approach for sample preparation (Elwin et al, 2014; Lindergard et al, 2003; Scharf et al, 2020; Shipley et al, 2022).…”
Section: Resultssupporting
confidence: 92%
“…For instance, while there is no significant difference (p > 0.05) in DNA yields between the DNA kits when no pretreatment is applied, the Powersoil Pro Kit produced higher DNA yields than the QIAamp DNA Mini kit when bead-beating pretreatment was conducted. This can be explained by the higher sensitivity and inhibitor removal technology attributed to this kit, as well as its associated 10-minute homogenization step (Amoah et al, 2019; Feng et al, 2023; Shipley et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Studies with the expressed goal of developing detection methods for C. cayetanensis specifically for soil are rare. Only one recent study described a method for the concentration of oocysts and molecular detection of C. cayetanensis in soil samples [ 97 ]. The study evaluated a concentration method using flotation in saturated sucrose solution and compared it to three commercial DNA isolation kits in experimentally seeded C. cayetanensis soil samples (5–10 g).…”
Section: Detection Methodsmentioning
confidence: 99%
“…Linearity of detection of the flotation method was observed and it was able to detect as few as 10 oocysts in 10 g of soil samples. This comparative study showed that the concentration of oocysts in soil samples by flotation in high-density sucrose solutions is an easy, low-cost, and sensitive method that could be implemented for the detection of C. cayetanensis in environmental soil samples [ 97 ]. The flotation method was able to detect low numbers of oocysts in two different types of farm soil (10 oocysts in 10 g of either type of farm soil) without modifications.…”
Section: Detection Methodsmentioning
confidence: 99%
“…Although there are some studies on the experimental conditions in which C. cayetanensis oocysts survive in the laboratory [ 6 , 7 ], unfortunately, there is no information on what triggers oocyst sporulation in field conditions. As is the case with other protozoa, C. cayetanensis oocysts are thought to be environmentally resistant; low numbers of oocysts with a heterogenous distribution are expected to be present in soil samples [ 8 , 9 ]. Thus, the detection of C. cayetanensis in soil usually requires concentration techniques which enrich the oocyst form of the parasite to enhance detection [ 9 ].…”
Section: Introductionmentioning
confidence: 99%